The Future of Resource-Based Theory - Barney, Jay B.; Ketchen, David J.; Wright, Mike (Journal of Management, 2011)
Since the 1991 publication of the first Journal of Management special issue devoted to resource-based inquiry, resource-based theory (RBT) has evolved from a nascent, upstart perspective to one of the most prominent and powerful theories for understanding organizations. Indeed, 20 years after that landmark issue, RBT appears to have reached maturity as a theory. One implication of this maturity is that RBT lies at a critical juncture, one that will be followed either by revitalization of the theory or by its decline. In this introductory article, the authors provide a brief overview of the contributions provided by the commentaries and articles contained in this third Journal of Management special issue on RBT. These contributions center on five themes: interlinkages with other perspectives, processes of resource acquisition and development, the micro-foundations of RBT, RBT and sustainability, and method and measurement issues. Their view is that the commentaries and articles collectively offer a foundation for extending RBT in meaningful new directions and steering clear of decline. They also offer their thoughts about some key opportunities within each of the themes for further revitalizing research involving the RBT.